Computational design and development of molecular imprint polymer for selective extraction of andrographolide from andrographis paniculata
This research study highlighted on computational design and molecular imprint polymer development for the extraction of andrographolide from Andrographis paniculata (A. Paniculata). Molecularly Imprinted Polymer (MIP) is one of the “Lock and Key” approach, where MIP is the lock and andrographolide is the key which fits the MIP lock both physically and chemically. Hyperchem 8.0.10 software was used to simulate and determine the suitable functional monomer and optimum template-functional monomer ratio for the best complexity among them. The MIPs were prepared by non-covalent precipitation polymerization. Andrographolide, methacrylic acid, and ethylene glycol dimethacrylate were used as template, functional monomer, and cross-linker, respectively. Non-imprinted polymer (NIP) was developed in the same manner as a control. The template molecules were removed from MIP polymer particles using methanol: acetic acid (1:1 v/v) solvent. MIP and NIP were characterized by Fouriertransform Infrared Spectroscopy, Scanning Electron Microscope and dynamic asorption study. The efficiency of andrographolide imprinted MIP were evaluated in separation and sensor applications. For the separation analysis, rebinding assay and adsorption isotherm studies were conducted. The imprinting factor of MIP is 2.26 with cavities distribution of 55.45 ml.g-1. The binding assay was analyzed by three types of non-linear adsorption isotherm. The developed MIP follows Langmuir-Freundlich isotherm with maximum binding capacity of 149.59 μg.g-1 where the experimental binding capacity was calculated as 167.86 μg.g-1. MIP-SPME was used to extract andrographolide from A. paniculata with 92.3 % of recovery. The LOD and LOQ of MIP-SPME is 0.14 and 0.466 μg.ml-1, respectively. MIP was applied in sensor development using Quartz Crystal Microbalance (QCM) 200 where MIP was electrodeposited using cyclic voltammetry. QCM 200 device gives the frequency changes corresponding to the selective adsorption of andrographolide from A. panciulata. The maximum binding sites on the MIP-QCM sensor by applying linear Langmuir isotherm is 18.02 ng.cm-2. In addition, MIP-QCM sensor could be used in real sample analysis. It was found that 45.53 % of andrographolide detected in 0.10 μg.ml-1 of plant extract with LOD and LOQ of 1.206 ng.cm-2 and 4.020 ng.cm-2 respectively. This is the first research using MIP based QCM sensor for the quantification of andrographolide from A. paniculata. This project demonstrated that the andrographolide imprinted polymer can be applied both in analytical separation and sensor development for the detection and quantification of andrographolide from A. paniculata plant extract. Therefore, a novel molecular imprint polymer was synthesized by precipitation polymerization which could be applied in separation and sensor studies